Assessing the integrated conservation effectiveness of protected areas on forest ecosystems in the Three Parallel Rivers Region, China - Bingran Ma; Hua Shen; Chunting Feng; Weiyang Zhao; Wei Wang (Ecological Indicators, 2025)
Protected areas (PAs) are critical for safeguarding biodiversity and maintaining ecosystem services. Assessing the conservation effectiveness of PAs in preserving forest ecosystem is of considerable significance in promoting management and policy recommendations of PAs. However, studies on the integrated effectiveness of PAs in enhancing forest coverage, improving forest ecosystem services, and mitigating forest fragmentation remains relatively limited. In this study, we chose three indicators include fraction vegetation coverage (FVC), forest fragmentation index (FFI), and ecosystem services (ESs, including water retention, soil conservation, carbon sequestration, and habitat quality) to investigate the conservation effectiveness of PAs in preserving forest ecosystems within the Three Parallel Rivers Region (TPRR), China. The results indicated that during the past two decades (2001–2020), 48.81%, 52.11%, and 59.82% of the areas within PAs showed positive or stable trends in FVC, FFI, and ESs, respectively. The integrated assessment revealed mixed results: 33.03% of the area within PAs achieved high conservation effectiveness, while 60.73% showed medium effectiveness. Overall, while 93.76% of the area showed a positive trend in at least one of the three indicators, this highlights the complex trade-offs in conservation outcomes. Moreover, the influencing factors of integrated conservation effectiveness were analyzed using the random forest model, revealing that natural factors and the size of protected areas had the greatest impact. To further enhance overall conservation effectiveness, more stringent management measures should be implemented at the local level nature reserves in this region. This multi-indicator assessment reveals the complexity of forest ecosystems across different regions, which facilitates the incorporation of additional indicators and provides guidance for a more comprehensive evaluation of the conservation effectiveness of diverse natural ecosystems in future research.